The Influence Of Local Wisdom And Promotion On The Purchase Decisions Of Culinary Foods By Generation Z In Denai Lama Tourism Village - Larasati Br. Br. Siagian; Adelina Lubis; Ikbar Pratama (UNIVED Press, 2026)
This research aims to determine the